KONSTRUK MODEL KEPEMIMPINAN KEPALA SEKOLAH DI DAERAH PEDESAAN CONSTRUCT OF PRINCIPAL LEADERSHIP MODELS IN RURAL AREAS - Diana Kurniawati; Burhanuddin Burhanuddin; Asep Sunandar (Universitas Negeri Malang, 2019)
Abstrac: The leadership of the head of the school is the effort to achieve the goals of education and carry out educational programs in order to improve the quality of education. To achieve the vision and mission of the school of motivation in work so that teachers have good performance learning process. The gap is found at the moment is the principal have not showed the applicability of management education in schools in rural areas. This research aims to know the factors which form the principal leadership in rural areas, see invalid constructs of motivation and the factors that affect the performance of teachers in rural invalid constructs. Then to describe the influence of principal leadership and motivation against the performance of primary school teachers in the Blitar. The research design used was descriptive korelasional. Results of the study of leadership high school principal (46.7%), motivation levels are (56.7%), a high level of teacher performance (44.4%) There is a positive influence provided leadership and motivation against the performance of teachers. The influence of the leadership after invalid constructs models made on performance and path analysis gained 0.68 β value. For motivation on performance of teachers acquire the value of β 0.6. So the factors that can affect the performance of primary school teachers such as leadership, and motivation.Keywords: leadership, motivation, performanceAbstrak: Penelitian ini bertujuan mengetahui faktor yang membentuk kepemimpinan kepala sekolah di daerah pedesaan, melihat konstruk motivasi dan faktor yang mempengaruhi konstruk kinerja guru di pedesaan. Kemudian untuk mendeskripsikan pengaruh kepemimpinan kepala sekolah dan motivasi terhadap kinerja guru sekolah dasar (SD) di Kabupaten Blitar, populasi penelitian sejumlah 106 diambil sampel 180 responden dari 20 SD di Kec Garum dan Kec. Gandusari. Desain penelitian yang digunkan adalah deskriptif korelasional. Hasil penelitian kepemimpinan kepala sekolah tinggi (46,7%), tingkat motivasi sedang (56,7%), tingkat kinerja guru tinggi (44,4%) ini terdapat pengaruh positif yang diberikan kepemimpinan dan motivasi terhadap kinerja guru. Pengaruh kepemimpinan setelah dibuat model konstruk terhadap kinerja dan path analysis memperoleh nilai β 0,68. Untuk motivasi terhadap kinerja guru memperoleh nilai β 0,6. Sehingga faktor yang dapat mempengaruhi kinerja guru SD diantaranya adalah kepemimpinan, dan motivasi.Kata Kunci: kepemimpinan, motivasi, kinerja